2016
DOI: 10.1186/s13018-016-0418-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic sleep deprivation on bone mass and bone metabolism in rats

Abstract: BackgroundThis study aimed to assess the effects of chronic sleep deprivation (CSD) on bone mass and bone metabolism in rats.MethodsTwenty-four rats were randomly divided into CSD and control (CON) groups. Rats were subjected to CSD by using the modified multiple platform method (MMPM) to establish an animal model of CSD. Biochemical parameters such as levels of serum N-terminal propeptide of type I procollagen (PINP), N-terminal cross-linking telopeptide of type I collagen (NTX), growth hormone (GH), estradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 49 publications
1
29
0
3
Order By: Relevance
“…In that study, the lower levels of bone formation markers and higher levels of bone resorption markers resulted in lower BMD in sleep-restricted rats compared with controls [9]. Chronically sleep-deprived female rats had lower bone formation marker levels after 1 month and lower bone resorption markers after 3 months [10]. Over time, the chronically sleeprestricted rats had lower BMD and poorer bone microarchitecture compared with controls [10].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In that study, the lower levels of bone formation markers and higher levels of bone resorption markers resulted in lower BMD in sleep-restricted rats compared with controls [9]. Chronically sleep-deprived female rats had lower bone formation marker levels after 1 month and lower bone resorption markers after 3 months [10]. Over time, the chronically sleeprestricted rats had lower BMD and poorer bone microarchitecture compared with controls [10].…”
Section: Introductionmentioning
confidence: 81%
“…Chronically sleep-deprived female rats had lower bone formation marker levels after 1 month and lower bone resorption markers after 3 months [10]. Over time, the chronically sleeprestricted rats had lower BMD and poorer bone microarchitecture compared with controls [10].…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, other clinical surveys showed that patients with SD have lower BMD (9)(10)(11). An animal study showed that SD affects bone health by decreasing BMD and 25(OH)D (12). The study also demonstrated that SD affected BMD by decreasing osteogenesis and impairing mineralization of the newly formed bones.…”
Section: Introductionmentioning
confidence: 84%
“…Significant relationships between depression, bone mineral density, and cortisol levels have been reported where depressed patients were shown to have higher cortisol levels and lower bone mineral density compared to placebo controls . Also, lifestyle that includes sleep disruption through shift work, sleep deprivation, physical strength, weight gain, and stress levels can adversely affect bone. Besides improving compliance, the positive effect of melatonin on mood and sleep may show benefits to bone by reducing cortisol levels and re‐entraining sleep/wake cycles to coincide with the light/dark cycle and natural bone rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…Significant relationships between depression, bone mineral density, and cortisol levels have been reported, and so any improvement in any of these variables could also contribute to melatonin's beneficial effects on bone. Therefore, the daily diary logs kept by the MOPS cohort were further analyzed to provide additional data to explain melatonin's beneficial actions (eg, lifestyle, mood, sleep) on bone as described in other studies …”
Section: Introductionmentioning
confidence: 99%